Gilbert, Nigel; Troitzsch, Klaus (2005). Simulation for the Social Scientist - Miguel Quesada, Francisco J. (Papers. Revista de Sociologia, 2006)
Ressenya de l'obra de Nigel Gilbert i Klaus Troitzsch apareguda el 2005. Simulation for the Social Scientist. Buckingham: Open University Press (2a edición).